Efektivitas Pelatihan Kerja Dalam Meningkatkan Prestasi Kerja Karyawan - Alhidayatullah Alhidayatullah; Ade Sudarma; Muhammad Khairul Amal (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This research uses a questionnaire and a quantitative approach to be descriptive. This study aims to ascertain how each independent variable, training instructors, training participants, training materials, training methods, and training objectives affects CV Agung Dipo Persada Sukabumi employees' work performance. Multiple linear regression analysis was used to analyze the data based on partial tests of training instructor variables, training materials, training methods, and training purposes. The results showed that the trainee variables had no significant impact on employee work performance. There is a positive and significant influence on employee work performance simultaneously (Test F) among training instructors, participants, training materials, training methods, and training objectives, with a test F value of sig value 0.000 < 0.05, and the R Square test returned a value of 0.585. This indicates that the independent variable can explain 58.5 percent of the employee's work performance, while other variables can explain 41.5 percent.